Professional self-actualisation of pharmacists in the United Arab Emirates: a pilot study - A. Abd Al Magied; K. Beyene; E. Arafa; A. Elnour; N. Kheir (Journal of Pharmaceutical Policy and Practice)
Objective This pilot study evaluated the professional self-actualisation (PSA) of pharmacists in the United Arab Emirates (UAE) across various practice settings.Methods Our study was conducted in the UAE from February to May 2024 and targeted pharmacists in hospitals, community pharmacies, industry, and academia. A PSA questionnaire was developed using validated instruments and expert input, and included items on professional fulfilment (PF), societal acceptance (SA), work environment (WE), autonomy and professional opportunities (APO), involvement in professional advocacy (IPA), and the impact of work on personal relationships (IWPR).Results Sixty-eight responses were received from pharmacists working in the community, hospital, industry and academic sectors. No significant differences in self-actualisation were observed between genders. PF scores were consistent across age groups, and education level significantly impacted IPA scores, with MSc/PhD holders (mean = 3.6, SD = 0.7) scoring higher than Bachelor's degree holders (mean = 2.9, SD = 0.9; p = 0.008). Years of experience were significantly associated with SA scores (p = 0.046), with pharmacists having 5–10 years of experience (mean = 3.5, SD = 0.8) scoring higher than those with less than 5 years (mean = 3.1, SD = 0.9) or more than 10 years (mean = 2.9, SD = 0.7). PF showed a strong correlation with a supportive WE (r = 0.744), highlighting the crucial role of a positive work setting in professional self-actualisation.Conclusion This study identified key factors affecting pharmacists’ self-actualisation in the UAE, emphasising the importance of a supportive work environment, recognition, and professional development for job satisfaction. Despite limitations such as low sample size and underrepresentation of certain sectors, the findings provide a basis for future research and inform strategies to enhance work environments, policies, and pharmacists’ professional satisfaction.